(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Palmo-plantar Psoriasis is a non-infectious chronic inflammatory disease of skin characterized by well defined erythmatous plaques with silvery scales which have a predilections for extensor surface and by chronic fluctuating course. Palmo-plantar Psoriasis is limited to the area of palm and soles. In Ayurveda all skin diseases are described under single heading i.e. Kushtha. Although there seems no direct correlation between disease described in Ayurveda but it can be correlated with Vipadika which is one type of Kshudrakushtha. The disease not only affects the patient physically but also disturbs mental and social health of the patient, as the appearance of patient may be embarrassing. Exact cause for this disease is unknown but there is an inherited predisposition. But According to Ayurved, its spreading because of unstable lifestyle changes such as dietary pattern, busy schedule and stressful lifestyle. As per Ayurvedic view point Vata, Kapha and Pitta/Rakta vitiation are the major contributing pathological factors in its manifestation. Virechan karma (purgation therapy) and internal medication is considered as the best line of management for skin disorders. The treatment options available in modern medicine are not satisfactory. A case report of 23 year old male presented with C/O well demarcated raised scaling of bilateral palms and soles with severe itching since 3 years is presented in this article which got significantly relief by adopting systematic Ayurvedic approach of Kushtha line of treatment by doing Shodhana and Shamana chikitsa. Shodhan chikitsa helps in expelling the Doshas and Shaman chikitsa balances the remaining Doshas.